FRACTAL FORECASTING FINANCIAL MARKET FOREX - D. Chikatueva; A. Silchenko; T. Rachkova; K. Orobets (Вестник Северо-Кавказского федерального университета)
This article focuses on the use of the fractal method in the financial market. Describes a brief history of the emergence of the term "fractal", the use of the fractal method and its properties. The list of advantages and opportunities of this method in the internationalfinancial market Forex is given. A review of the factors, as well as the degree of their influence on the fractal analysis. Proven fractal relationships between prices on exchanges and repetitive structures through the use of computer simulation programs. Were considered trading strategies and features of their use.